Generalized cutaneous morphea in a patient with post-hepatitis C cirrhosis - Badri, Talel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
A case of generalized cutaneous morphea in a a 55-year-old female patient known to have suffered 10 years from post-hepatitis C virus cirrhosis is reported. Anti-HCV antibodies were present, whereas screening for HBs antigen and anti-HBc antibodies was negative.
Keywords: ciroza jeter; Hepatitis C; Jetra, ciroza; kožne spremembe; Liver Cirrhosis; Middle Age; Scleroderma, Circumscribed; sklerodermija; Sklerodermija cirkumskriptna; Srednja leta; virusne infekcije